Mammal distributions in the western Mediterranean: the role of human intervention ... - Dobson, M. (Zenodo, 1998)
(Uploaded by Plazi for the Bat Literature Project) The natural distribution of the 17 non-flying mammal species occurring wild in both the Maghreb (north-west Africa) and Iberia (south-west Europe) is considered. It is concluded that only four species – Red Fox Vulpes vulpes, Wild Boar Sus scrofa, Wild Cat Felis silvestris and Otter Lutra lutra – are native to both regions, while another three – Red Deer Cervus elaphus, Brown Bear Ursus arctos and Aurochs Bos primigenius – were native to North Africa until the mid-Holocene but have probably died out naturally. Algerian Hedgehog Atelerix algirus, Barbary Ape Macaca sylvanus, Genet Genetta genetta and Egyptian Mongoose Herpestes ichneumon are widely accepted as introductions to Europe from North Africa. The remaining six species, and Red Deer now found in Africa, were also probably introduced – Rabbit Oryctolagus cuniculus, Weasel Mustela nivalis, Wood Mouse Apodemus sylvaticus and Lesser White-toothed Shrew Crocidura russula from Europe to Africa; Algerian ...